A program to train medical physicists for direct patient care responsibilities. (17th October 2018) - Brown, Derek W.; Atwood, Todd F.; Moore, Kevin L.; MacAulay, Robert; Murphy, James D.; Mundt, Arno J.; Pawlicki, Todd
Abstract: Objectives: To develop a training program designed to meet the specific needs of medical physicists as they transition into a clinical role with direct patient care responsibilities. Materials and Methods: The training program was designed in collaboration with the faculty at the UC San Diego School of Medicine and incorporates training techniques that have been shown to be effective in improving communication skills. The program emphasizes experiential, practice‐based learning over didactic presentations. Results: The training program is comprised of 5 components: 1) a 1‐day Clinician‐Patient Communication Workshop run by the UC San Diego School of Medicine, 2) Communication Strategies for Radiation Oncology, which consists of two, 2‐hour sessions designed to provide trainees with patient communication skills that are specific to patient interactions in radiation oncology, 3) Simulated Patient Interactions, in which trainees perform mock physicist‐patient consults with trained patient actors, 4) Faculty‐Observed Patient Consults, and 5) a Case‐Based Treatment Toxicity Course. A competency assessment mechanism was also developed to provide a clear set of objectives and to guide trainer feedback. [Correction added after first online publication on November 8, 2018: The phrase ", which consists of two, 2‐hour" was added above.] Conclusions: The training program that we have developed incorporates an array of established education techniques and provides a comprehensive, accessible, means of improving medical physicists' patient communication skills.